Selling Hotel Kinara : valuing commercial property during an economic crisis - Das, Prashant, (SAGE Business cases., 2024)
The case is centred around valuing a commercial property asset in different market conditions using the discounted cash flow method. Students develop a cash flow pro forma on the basis of market information. The case exposes students to several nuances of pro forma development. Students are sensitised to the idea that valuation is about not just cash flows but also the perceived risk in cash flows. The perceived risks may result from investors' overreaction to market conditions and irrational sentiments. The discount rate, capitalisation rate, etc. must be revised carefully as the market cycles change.